AB0171 Impact of degenerative radiological abnormalities and vertebral fractures on the evaluation of spinal bone density in women with osteoporosis. (1st June 2001) - Paiva, L; Filardi, S; Pinto-Neto, AM; Samara, A; Marques-Neto, JF
Abstract : Background: Osteophytes and lumbar spine fractures can hinder bone density interpretation. Objectives: The objective of this study was to establish the relationship between densitometric measurements and degenerative radiological findings of the lumbar spine, in women with osteoporosis. Methods: The study consisted of ninety-six postmenopausal women presenting osteoporosis in their lumbar spine bone density, DEXA, LUNAR-DPX. Fractures, osteophytes and aortic calcifications were evaluated by simple x-rays of thoracic and lumbar spine. Results: The X-rays confirmed lumbar fractures in 24.7%, osteophytes in 33.3% and calcifications of the aorta in 30.2%. The mean BMD was 0.783 g/cm 2 and the mean T-score was ?3.47 DP. Neither fractures, nor aortic calcifications had significant influence on BMD (p = 0, 36 e p = 0, 09 respectively) despite the fractured vertebrae having greater BMD (p < 0, 02). Patients with lumbar spine osteophytes showed greater BMD (p = 0, 04). Only osteophytosis was associated to lumbar spine BMD (p = 0, 008). Conclusion: Osteophytes and lumbar spine fractures can hinder bone density interpretation. Based on these findings, the interpretation of densitometric results should be carried out together with that of a simple lumbar spine X-ray. References: Heaney RP, Recker RR, Saville PD. Menopasal changes in bone remodeling. J Lab Clin Med. 1978;92:953–63 Kleerekoperm KS. Metabolic bone diseases sec IV primer on the metabolic diseases and disorders of mineral metabolism . 4th edn. Philadephia: Lippincott Williams & Wilkins, 1999